2007
DOI: 10.1063/1.2709526
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation property of the magnetic-fluid-based fiber-optic evanescent field modulator

Abstract: The details about the modulation property of the magnetic-fluid-based fiber-optic evanescent field modulator are studied in this article. Experiments show that it needs some time for the outgoing light from the modulator to reach the final steady value when the external magnetic field is turned on or off (called the relaxation property of the modulator). Two exponential functions are employed to fit the experimental data of the falling and rising relaxation processes in order to achieve the falling and rising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(28 citation statements)
references
References 33 publications
1
26
0
1
Order By: Relevance
“…There are two main factors to determine the agglomeration or dispersion process of the magnetic chains, that is, magnetic attraction and thermal agitation. The former makes the magnetic particles to agglomerate while the latter makes the magnetic particles be dispersed (Pu et al 2007). In the experiment, the amplitude of the magnetic field remains unchanged and the temperature keeps rising so that the latter factor plays a role.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are two main factors to determine the agglomeration or dispersion process of the magnetic chains, that is, magnetic attraction and thermal agitation. The former makes the magnetic particles to agglomerate while the latter makes the magnetic particles be dispersed (Pu et al 2007). In the experiment, the amplitude of the magnetic field remains unchanged and the temperature keeps rising so that the latter factor plays a role.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al have proven that the magnetic-field-dependent optical transmission originates from the agglomeration of the magnetic particles that reduces the area of the liquid phase . Because the thermal agitation can suppress the ability of the agglomeration (Pu et al 2007), the optical transmission can be tuned by changing the ambient temperature around the ferrofluid. Based on this principle, a temperature sensor is suggested by using ferrofluid thin film with a constant external magnetic filed.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these are based on the fluid behavior and magnetism of the MF. Until now, several potential applications of MF to optical devices have been proposed, such as MF optical switches [11], MF gratings [12], MF light modulation [13], MF optical fiber modulator [14], and MF optical limiting [15]. Recently, some experimental investigations about the magneto-optical effects of binary, multiple-phase, ionic, and doped MFs show that these kinds of MFs can present some unique optical properties [16-19].…”
Section: Introductionmentioning
confidence: 99%
“…Although a variety of remarkable effects, such as Hall effect (Ren et al 2005), shear-excited sound (Muller and Liu 2002), one-dimensional patterns (Wirtz and Fermigier 1994), solitons (Richter and Barashenkov 2005) convective instabilities (Luo et al 1999) and thermal lens effect (Pu et al 2005) have been observed in magnetic fluid, and fibers with ''magnetic'' cores have been theoretically investigated (Reyes and Rodriguez 1997), there are also some reports about magnetic fluids have been used as cladding (Chieh et al 2007;Horng et al 2005;Pu et al 2007), but no attempts were made to explore novel effects in magnetic fluid core fiber. More surprising results may be anticipated when such distinctive fluid is combined with optical fibers, as light can be strongly confined in the waveguide here.…”
Section: Introductionmentioning
confidence: 99%